Lead-zinc tailing ceramsite and preparation method thereof
By using raw materials such as lead-zinc tailings, and using specific heating and cooling procedures, the problem of heavy metal pollution in lead-zinc tailings is solved, resource utilization and heavy metal curing are achieved, and high strength, low water absorption rate and good economic benefits are achieved.
Patent Information
- Application Number
- CN202411642746.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The storage of lead-zinc tailings leads to heavy metal pollution, and the existing technology is difficult to effectively solidify the heavy metals in it, affecting resource utilization.
Ceramic granules are prepared using raw materials such as lead-zinc tailings, limestone tailings, active mullite nanopowder, glass powder and dry sludge powder, and through specific heating and cooling procedures, ceramic granules with high strength and low water absorption are formed.
The resource utilization of lead-zinc tailings has been realized. Through the preparation of ceramite, heavy metals have been effectively cured, the strength and porosity of ceramite are improved, the water absorption rate is reduced, and there are good economic and social benefits.
Smart Images

Figure BDA0005138909240000051 
Figure BDA0005138909240000081 
Figure BDA0005138909240000082
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of resource recycling, and particularly relates to lead-zinc tailings ceramsite and a preparation method thereof. Background Art
[0002] Lead-zinc tailings are low-grade ores left after lead-zinc enterprises extract concentrates through flotation during the mining process. Most of them are mixed with sand and gravel into a slurry state. At present, the annual production of lead-zinc tailings in China has reached more than 20 million tons, and the stockpile volume is still rising. The stockpile of lead-zinc tailings and smelting slag will cause the diffusion of heavy metals. During the long-term accumulation process, the combined effects of internal and external factors will leach out harmful components of heavy metal liquids such as acidic water. These harmful components flow into surface rivers and infiltrate groundwater through rainwater scouring, causing serious heavy metal pollution in mining areas and even in a larger area of water resources. Therefore, the resource utilization of lead-zinc tailings is crucial.
[0003] At present, lead-zinc tailings are used as raw materials to produce cement, building wall materials, ceramsite, ceramics, glass, unburned wall bricks and artificial marble, etc., and because the components of lead-zinc tailings are similar to clay, it can be used as a clay ingredient to produce cement that meets national standards. However, due to the large amount of lead-zinc tailings and the high content of heavy metals, the solidification of heavy metals is an important direction in the process of resource utilization. Ceramsite is used in lead-zinc tailings as an important technical means of solidifying heavy metals. Therefore, the preparation of light aggregates using lead-zinc tailings as raw materials can promote the technological progress of lead-zinc tailings reduction, resource utilization, and harmless utilization, and promote the sustainable development of the lead-zinc tailings industry. Summary of the invention
[0004] In view of the problems in the prior art, the present invention provides a lead-zinc tailings ceramsite and a preparation method thereof.
[0005] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0006] A lead-zinc tailings ceramsite, mainly made of the following raw materials in parts by weight:
[0007] 100 parts of lead-zinc tailings;
[0008] 20-30 parts of limestone tailings;
[0009] 6-8 parts of active mullite nano powder;
[0010] 1-3 parts of glass powder;
[0011] 8 to 12 parts of dry sludge powder.
[0012] The active mullite nano powder is prepared by uniformly dispersing mullite particles in a mixed solution of sodium silicate and potassium silicate, heating the solution and then grinding the solution.
[0013] The mass ratio of the mullite particles to sodium silicate and potassium silicate is 1:(1-2):(3-5); the heating temperature is 300-600°C; and the particle size of the active mullite nanopowder is 200-400nm.
[0014] The heating temperature is 300-600°C because at this temperature sodium silicate and potassium silicate will lose bound water and gel properties, making them easier to grind. When the temperature is too low, they are difficult to grind.
[0015] The particle size of the active mullite nanopowder is 200-400 nm, because this particle size can achieve good encapsulation of the mullite nanoparticles by sodium / potassium silicate, while ensuring the integrity and activity stimulation effect of the mullite nanoparticles.
[0016] The particle size of the mullite particles is 50-100 nm, the concentration of the mixed solution of sodium silicate and potassium silicate is 5wt%-15wt%, and the modulus of the sodium silicate and potassium silicate is not higher than 2.
[0017] The modulus of sodium silicate and potassium silicate is not higher than 2 because the modulus is too high, the viscosity is too large, the mullite particles are unevenly dispersed, and the dissolution-promoting effect on silicon dioxide is poor at high temperature.
[0018] The specific surface area of the lead-zinc tailings is 800-1000m 2 / kg, because the specific surface area is too small, silica and alumina are difficult to dissolve and cannot form a strong structure, resulting in low strength.
[0019] The specific surface area of the limestone tailings is not less than 200m 2 / kg, because the specific surface area is too small and unevenly distributed inside the expanded clay, it is impossible to form a continuous and stable bonding structure, which will cause a decrease in strength.
[0020] The specific surface area of the glass powder is not less than 300m 2 / kg is to ensure uniform dispersion.
[0021] The specific surface area of the dry sludge powder is not less than 200m 2 / kg is to ensure uniform dispersion.
[0022] A method for preparing lead-zinc tailings ceramsite comprises the following steps:
[0023] (1) mixing lead-zinc tailings, limestone tailings, activated mullite nanopowder, glass micropowder and dry sludge powder raw materials uniformly according to parts by mass, and adding water to prepare a ceramsite embryo body;
[0024] (2) heating the ceramsite embryo to 900-980° C. and maintaining it for 5-8 min; then heating it to 1200-1300° C. and maintaining it for 8-10 min;
[0025] (3) Cooling to 1150-1100°C and maintaining for 5-10 min; then cooling to 1080-1000°C and maintaining for 5-10 min; then cooling to 950-900°C and maintaining for 5-10 min; finally, slowly cooling to room temperature to obtain lead-zinc tailings ceramsite.
[0026] The preparation method of the active mullite nano powder is as follows: after the mullite particles are evenly dispersed in a sodium silicate solution and a potassium silicate mixed solution, the particles are dried at a high temperature until the quality is stable, and then ground to 200-400nm under completely dry conditions to obtain the active mullite nano powder.
[0027] The reason why step (3) is to cool down and harden in stages is that direct cooling causes all materials that can produce a molten body to harden in a disordered manner, resulting in a large number of microcracks in the structure, which affects the structural strength and the water absorption of the ceramsite.
[0028] In step (3), the temperature is slowly cooled to room temperature at a rate of no more than 10°C / min because cracks are easily generated if the temperature is cooled too fast.
[0029] Beneficial effects:
[0030] (1) The present invention uses lead-zinc tailings as the main raw material to prepare lead-zinc tailings ceramsite. By compounding the lead-zinc tailings and the limestone tailings, the synergistic effect of the two tailings is achieved, and the resource utilization of the lead-zinc tailings and the limestone tailings is achieved, which has good economic and social benefits. The density grade of the ceramsite prepared by the present invention is 600-900, the cylinder pressure strength is 6.8-9.8MPa, and the water absorption rate is 9.4%-11.4%, which has good strength and low water absorption rate.
[0031] (2) The present invention uses sodium silicate and potassium silicate to modify and activate mullite particles to prepare active mullite nanopowder, which improves the dissolution rate and dissolution amount of active substances in lead-zinc tailings and improves the performance of lead-zinc tailings ceramsite. Using active mullite nanopowder as a seed effectively promotes the generation of mullite crystals in lead-zinc tailings ceramsite under high temperature conditions, and improves the bonding strength of inert particles in ceramsite.
[0032] (3) The present invention uses sludge powder and glass powder to provide sufficient molten silicon dioxide, which is conducive to the storage of bubbles in the molten glass body and improves the porosity of ceramsite. Sludge provides organic matter to generate gas at high temperature, which promotes the porous structure of ceramsite. The difference from limestone is that the temperature at which the organic matter in sludge burns to form pores is relatively low, mainly because the porous structure is left after the organic matter is burned. Limestone, on the other hand, generates gas that remains in the molten liquid formed after the glass powder is melted, forming bubbles.
[0033] (4) The present invention uses sludge powder to burn organic matter to generate gas, and calcium carbonate in limestone tailings decomposes at high temperature to generate carbon dioxide gas, thereby increasing the porosity of ceramsite. At the same time, the decomposed calcium oxide and silicon dioxide generate calcium silicate at high temperature, which wraps and adheres to the lead-zinc tailings particles, thereby increasing the strength of the ceramsite. DETAILED DESCRIPTION
[0034] The method of the present invention is described in detail below with reference to specific examples.
[0035] Example 1
[0036] A lead-zinc tailings ceramsite, mainly made of the following raw materials in parts by weight:
[0037] 100 parts of lead-zinc tailings;
[0038] 20 parts of limestone tailings;
[0039] 6 parts of active mullite nanopowder;
[0040] 3 parts of glass powder;
[0041] 8 parts of dry sludge powder.
[0042] The specific surface area of the lead-zinc tailings is 1000m 2 / kg, the specific surface area of limestone tailings is 200m 2 / kg, the specific surface area of glass powder is 300m 2 / kg.
[0043] The preparation method of the active mullite nano powder is as follows: after evenly dispersing mullite particles with a particle size of 80nm in a mixed solution of sodium silicate solution and potassium silicate with a concentration of 5wt%, heating to 300°C and drying until the quality is stable, grinding to 300nm under completely dry conditions, the mass ratio of mullite particles to sodium silicate and potassium silicate is 1:2:5.
[0044] The modulus of the sodium silicate is 2.0, and the modulus of the potassium silicate is 1.0.
[0045] The dry sludge powder is obtained by drying the sludge and grinding it into a powder with a specific surface area of 200m 2 / kg of powder.
[0046] The preparation method of lead-zinc tailings ceramsite is as follows: (1) the above raw materials are mixed evenly, 50 parts of water are added, and the ceramsite body is prepared by a granulator; (2) the ceramsite body is heated to 980°C and maintained for 5 minutes; then heated to 1300°C and maintained for 8 minutes; (3) the temperature is reduced to 1120°C and maintained for 7 minutes; then the temperature is reduced to 1050°C and maintained for 7 minutes; then the temperature is reduced to 920°C and maintained for 7 minutes; finally, the temperature is slowly reduced to room temperature at a rate of 5°C / min to obtain lead-zinc tailings ceramsite.
[0047] Example 2
[0048] A lead-zinc tailings ceramsite, mainly made of the following raw materials in parts by weight:
[0049] 100 parts of lead-zinc tailings;
[0050] 30 parts of limestone tailings;
[0051] 8 parts of active mullite nano powder;
[0052] 1 part of glass powder;
[0053] 12 parts of dry sludge powder.
[0054] The specific surface area of the lead-zinc tailings is 800m 2 / kg, the specific surface area of limestone tailings is 300m 2 / kg, the specific surface area of glass powder is 400m 2 / kg.
[0055] The preparation method of the active mullite nano powder is as follows: after evenly dispersing mullite particles with a particle size of 100nm in a mixed solution of sodium silicate solution and potassium silicate with a concentration of 15wt%, heating to 600°C and drying until the quality is stable, grinding to 400nm under completely dry conditions, the mass ratio of mullite particles to sodium silicate and potassium silicate is 1:1:3.
[0056] The modulus of the sodium silicate is 1.0, and the modulus of the potassium silicate is 1.0.
[0057] The dry sludge powder is obtained by drying the sludge and grinding it into a powder with a specific surface area of 300m 2 / kg of powder.
[0058] The preparation method of lead-zinc tailings ceramsite is as follows: (1) the above raw materials are mixed evenly, 40 parts of water are added, and the ceramsite body is prepared by a granulator; (2) the ceramsite body is heated to 900°C and maintained for 8 minutes; then heated to 1200°C and maintained for 10 minutes; (3) the temperature is reduced to 1150°C and maintained for 5 minutes; then the temperature is reduced to 1080°C and maintained for 5 minutes; then the temperature is reduced to 950°C and maintained for 5 minutes; finally, the temperature is slowly reduced to room temperature at a rate of 10°C / min to obtain lead-zinc tailings ceramsite.
[0059] Example 3
[0060] A lead-zinc tailings ceramsite, mainly made of the following raw materials in parts by weight:
[0061] 100 parts of lead-zinc tailings;
[0062] 25 parts of limestone tailings;
[0063] 7 parts of active mullite nano powder;
[0064] 2 parts of glass powder;
[0065] 10 parts of dry sludge powder.
[0066] The specific surface area of the lead-zinc tailings is 900m 2 / kg, the specific surface area of limestone tailings is 400m 2 / kg, the specific surface area of glass powder is 450m 2 / kg.
[0067] The preparation method of the active mullite nano powder is as follows: after evenly dispersing mullite particles with a particle size of 50nm in a mixed solution of sodium silicate solution and potassium silicate with a concentration of 10wt%, heating to 400°C and drying until the quality is stable, grinding to 200nm under completely dry conditions, the mass ratio of mullite particles to sodium silicate and potassium silicate is 1:1.5:4.
[0068] The modulus of the sodium silicate is 1.5, and the modulus of the potassium silicate is 1.5.
[0069] The dry sludge powder is obtained by drying the sludge and grinding it into a powder with a specific surface area of 350m 2 / kg of powder.
[0070] The preparation method of lead-zinc tailings ceramsite is as follows: (1) the above raw materials are mixed evenly, 48 parts of water are added, and the ceramsite body is prepared by a granulator; (2) the ceramsite body is heated to 950°C and maintained for 6 minutes; then heated to 1250°C and maintained for 9 minutes; (3) the temperature is reduced to 1100°C and maintained for 10 minutes; then the temperature is reduced to 1000°C and maintained for 10 minutes; then the temperature is reduced to 900°C and maintained for 10 minutes; finally, the temperature is slowly reduced to room temperature at a rate of 3°C / min to obtain lead-zinc tailings ceramsite.
[0071] The performance indicators of the expanded clay of Examples 1 to 3 were tested according to the provisions of GB / T 17431.1-2010 “Light aggregate and its test methods Part 1 Light aggregate”, and the results are shown in Table 1.
[0072] Table 1 Performance indexes of Examples 1 to 3 ceramsite
[0073] serial number Density level Cylinder pressure strength / MPa Water absorption / % Example 1 900 9.8 9.8 Example 2 600 6.8 11.4 Example 3 800 8.2 9.4
[0074] As shown in Table 1, in Examples 1 to 3, the density grade of the ceramsite is 600 to 900, the cylinder pressure strength is 6.8 to 9.8 MPa, and the water absorption rate is 9.4% to 11.4%, indicating that the ceramsite of the present invention can achieve a high cylinder pressure strength and a low water absorption rate between the density grade of 600 to 900, and achieves a good preparation of the lead-zinc tailings ceramsite. From the changes in the density grade and the cylinder pressure strength, it can be seen that the difference mainly comes from the content of dry sludge powder. The higher the dry powder sludge content, the higher the organic matter content, and the more gas is generated under high temperature conditions, which makes the cylinder pressure strength of the ceramsite decrease and the water absorption rate increase. However, under the dry powder sludge content controlled by the present invention, it can be ensured that the lead-zinc tailings ceramsite achieves relatively ideal mechanical properties and water absorption rate.
[0075] Comparative Example 1
[0076] The difference from Example 3 is that the specific surface area of the lead-zinc tailings is 600m 2 / kg.
[0077] Comparative Example 2
[0078] The difference from Example 3 is that the specific surface area of the lead-zinc tailings is 1200m 2 / kg.
[0079] The performance of the ceramsite of Comparative Examples 1 to 2 was tested, and the results are shown in Table 2.
[0080] Table 2 Performance indexes of comparative examples 1 to 2 ceramsite
[0081]
[0082] It can be seen from the comparison of Comparative Examples 1 to 2 in Table 2 with Example 3 that when the specific surface area of the lead-zinc tailings is large, its cylinder pressure strength decreases and the water absorption rate increases. This is mainly because there are a large number of inert particles in the lead-zinc tailings, and the particles are too small, resulting in increased shrinkage, increased microcracks, poor structural stability, decreased strength, and increased water absorption rate. When the specific surface area of the lead-zinc tailings is small, its cylinder pressure strength decreases and the water absorption rate increases. When the specific surface area is small, the glass melt is less and difficult to melt out, and the bonding strength is low, resulting in a low cylinder pressure strength. Therefore, selecting a lead-zinc tailings with a suitable specific surface area can obtain ceramsite with better performance.
[0083] Comparative Example 3
[0084] The difference from Example 3 is that no limestone tailings are added.
[0085] Comparative Example 4
[0086] The difference from Example 3 is that 10 parts of limestone tailings are added.
[0087] Comparative Example 5
[0088] The difference from Example 3 is that 40 parts of limestone tailings are added.
[0089] The performance of the ceramsite of Comparative Examples 3 to 5 was tested, and the results are shown in Table 3.
[0090] Table 3 Performance indexes of comparative examples 3 to 5 ceramsite
[0091] serial number Limestone tailings Density level Cylinder pressure strength / MPa Water absorption / % Example 3 25 800 8.2 9.4 Comparative Example 3 0 800 4.3 23.5 Comparative Example 4 10 800 5.3 14.7 Comparative Example 5 40 800 5.6 13.8
[0092] From the comparison of Table 3 Comparative Examples 3 to 5 and Example 3, it can be seen that with the increase in the amount of limestone tailings, the strength of the lead-zinc tailings ceramsite first increases and then decreases, and the water absorption first decreases and then increases. The performance of the ceramsite in Example 3 is the best. This is mainly because the limestone tailings provide calcium carbonate, which decomposes at high temperature to produce gas, promotes the porous structure of the ceramsite, and reduces the strength. After calcium carbonate decomposes and produces carbon dioxide between 900 and 980°C, it forms calcium oxide. At the same time, calcination at 1200 to 1300°C just uses calcium oxide and molten silicon dioxide to form calcium silicate, and then slowly cools the calcium silicate to harden and form a gel structure. Under this condition, due to the formation of calcium silicate consuming silicon dioxide, under the dissolution promoting effect of potassium silicate and sodium silicate, more silicon dioxide in the lead-zinc tailings is dissolved, which improves the bonding strength of the ceramsite glass body and reduces the water absorption rate. Therefore, the influence of limestone on the mechanical properties and water absorption rate of ceramsite after incorporation is positive and negative. When the limestone content is low, as its content increases, the gas generated by high temperature increases, causing the porosity of the ceramsite structure to increase, which will cause the strength to decrease. However, the calcium silicate formed at 1200-1300℃ increases the structural strength, which can completely compensate for the strength decrease caused by the increase in gas. At the same time, because when the gas content is small, most of the generated pores are closed, so it will not lead to an increase in water absorption. On the contrary, the increased structural density of calcium silicate makes its water absorption rate decrease. However, when the content is too high, the negative effect caused by excessive pores generated by gas increases, making the generated calcium silicate unable to compensate for the strength loss caused by the increase in gas, causing the strength of the ceramsite to decrease and the water absorption rate to increase. At the same time, too much gas produces connected pores, causing the water absorption rate to increase. Therefore, choosing the appropriate limestone tailings content can obtain ceramsite with better performance.
[0093] Comparative Example 6
[0094] The difference from Example 3 is that the particle size of the mullite is 200 nm.
[0095] The performance of the ceramsite of Comparative Example 6 was tested, and the results are shown in Table 4.
[0096] Table 4 Performance indexes of comparative example 6 ceramsite
[0097] serial number Mullite particle size (nm) Density level Cylinder pressure strength / MPa Water absorption / % Example 3 50 800 8.2 9.4 Comparative Example 6 200 800 6.4 17.9
[0098] It can be seen from the comparison of Table 4 Comparative Example 6 and Example 3 that the cylinder pressure strength of Comparative Example 6 decreases and the water absorption rate increases. This shows that nano-mullite can play a seeding role. When the seed size increases, its nucleation effect decreases, so that the mullite formed under high temperature conditions is reduced. Mullite mainly plays the role of bonding particles to improve strength. Its generation is reduced, then the strength decreases and the water absorption rate increases.
[0099] Comparative Example 7
[0100] The difference from Example 3 is that only sodium silicate is used in the active mullite nanopowder, and the process of cooling to 920° C. and maintaining for 7 minutes in step (3) is omitted.
[0101] Comparative Example 8
[0102] The difference from Example 3 is that only potassium silicate is used in the active mullite nanopowder, and the process of cooling to 1050° C. and maintaining for 7 minutes in step (3) is omitted.
[0103] The performance of the ceramsite of Comparative Examples 7 to 8 was tested, and the results are shown in Table 5.
[0104] Table 5 Performance indexes of comparative examples 7 to 8 ceramsite
[0105] serial number Nano-mullite modified Density level Cylinder pressure strength / MPa Water absorption / % Example 3 Sodium silicate, potassium silicate 800 8.2 9.4 Comparative Example 7 Sodium silicate 800 6.2 16.5 Comparative Example 8 Potassium silicate 800 6.1 16.0
[0106] From the comparison of Comparative Examples 7 to 8 in Table 5 and Example 3, it can be seen that the use of either sodium silicate or potassium silicate alone for modification and activation of nano-mullite activity will cause its cylinder pressure strength to decrease and its water absorption to increase. This shows that the use of mutual mixing can increase the temperature gradient of vitreous dissolution during the reaction, which is beneficial to improving the stability of the structure, and the use of mutual mixing has a better dissolution-promoting effect.
[0107] Comparative Example 9
[0108] The difference from Example 3 is that the active mullite nanopowder is ground to 100 nm.
[0109] The performance of the ceramsite of Comparative Example 9 was tested, and the results are shown in Table 6.
[0110] Table 6 Performance indexes of comparative example 9 ceramsite
[0111]
[0112] As can be seen from the comparison of Table 6 Comparative Example 9 and Example 3, active mullite nano powder grinding to 100nm is not conducive to strength improvement and water absorption rate decline. This is because the purpose of active mullite powder preparation is to form an overall structure after sodium silicate / potassium and mullite nano powder are mixed, and sodium silicate / potassium belongs to alkalinity at the same time, which can reduce the mullite formation temperature and promote mullite generation. When the sodium silicate / potassium dissolution promoting effect occurs under high temperature conditions, fused silicon dioxide and aluminum oxide quickly generate mullite structure under the effect of mullite seed, improving ceramsite structural strength. When grinding is too fine, it is easy to cause the composite structure formed by mullite powder and sodium silicate / potassium to be destroyed, and sodium silicate / potassium and mullite nano separation cannot play a good promotion effect.
[0113] Comparative Example 10
[0114] The difference from Example 3 is that the modulus of sodium silicate and potassium silicate in the active mullite nanopowder is 3.0.
[0115] The performance of the ceramsite of Comparative Example 10 was tested, and the results are shown in Table 7.
[0116] Table 7 Performance indexes of comparative example 10 ceramsite
[0117]
[0118] From the comparison of Comparative Example 10 and Example 3 in Table 7, it can be seen that the cylinder pressure strength of Comparative Example 10 decreases and the water absorption rate increases. This is because the modulus of sodium / potassium silicate is too high, resulting in excessively high viscosity and uneven dispersion, and the dissolution-promoting effect decreases in the later stage, resulting in reduced strength.
[0119] Comparative Example 11
[0120] The difference from Example 3 is that in step (3), the final slow cooling to room temperature is performed at a rate of 20°C / min.
[0121] Comparative Example 12
[0122] The difference from Example 3 is that the temperature is directly lowered to room temperature during the cooling process.
[0123] The performance of the ceramsite of Comparative Examples 11 to 12 was tested, and the results are shown in Table 8.
[0124] Table 8 Performance indexes of comparative examples 11 to 12 ceramsite
[0125]
[0126]
[0127] From the comparison of Comparative Examples 11 to 12 in Table 8 and Example 3, it can be seen that the cooling speed of Comparative Example 11 is too fast, the cylinder pressure strength decreases, and the water absorption rate increases. This is because the cooling is too fast, the shrinkage is uneven, the volume stability is reduced, cracks are easily generated, and the water absorption rate increases and the strength decreases. Comparative Example 12 is directly cooled to room temperature without a staged stop in the middle time period, which will lead to structural instability and unstable shrinkage, resulting in a decrease in structural strength and an increase in water absorption.
[0128] Comparative Example 13
[0129] The difference from Example 3 is that the temperature is directly raised to 1250°C.
[0130] Comparative Example 14
[0131] The difference from Example 3 is that the maximum temperature of the heating is 1180°C.
[0132] The performance of the ceramsite of Comparative Examples 13 to 14 was tested, and the results are shown in Table 9.
[0133] Table 9 Performance indexes of comparative examples 13 to 14 ceramsite
[0134]
[0135] From the comparison of Comparative Examples 13-14 and Example 3 in Table 9, it can be seen that when Comparative Example 13 is directly heated to the maximum temperature of 1250°C, the molten glass will be dissolved too concentratedly, the bubbles will be generated too concentratedly, the bubbles will be generated fiercely, the bubbles will merge to form large bubbles, and a large number of bubbles will overflow, resulting in high density and reduced strength. The maximum temperature of the heating in Comparative Example 14 is 1180, which leads to a significant decrease in strength and an increase in water absorption. This is because calcination at 1200-1300°C just uses calcium oxide and molten silicon dioxide to form calcium silicate, and then slowly cools the calcium silicate to harden and form a gel structure. Under this condition, since the formation of calcium silicate consumes silicon dioxide, more silicon dioxide in the lead-zinc tailings is dissolved under the dissolution-promoting effect of potassium silicate and sodium silicate, which improves the bonding strength of the ceramsite glass and reduces the water absorption. When the temperature is not reached, calcium silicate cannot be formed, resulting in a large amount of calcium oxide powder in the product, which not only makes the structure have poor adhesion, but also easily absorbs water in the air, causing the structure to expand and destroy, resulting in a decrease in the performance of the expanded clay.
[0136] Comparative Example 15
[0137] The difference from Example 3 is that no active mullite nanopowder is added.
[0138] Comparative Example 16
[0139] The difference from Example 3 is that 3 parts of active mullite nanopowder are added.
[0140] The performance of the ceramsite of Comparative Examples 15 to 16 was tested, and the results are shown in Table 10.
[0141] Table 10 Performance indexes of comparative examples 15 to 16 ceramsite
[0142] serial number Active mullite nano powder content Density level Cylinder pressure strength / MPa Water absorption / % Example 3 7 servings 800 8.2 9.4 Comparative Example 15 0 copies 900 6.3 14.8 Comparative Example 16 3 servings 800 3.9 29.3
[0143] From the comparison of Comparative Examples 15-16 and Example 3 in Table 10, it can be seen that the absence of active mullite nanopowder in Comparative Example 15 and the addition of a small amount of active mullite nanopowder in Comparative Example 16 will lead to a significant decrease in strength and an increase in water absorption. This is mainly because the active mullite nanopowder plays a role in crystal nucleation and dissolution promotion. If it is not added sufficiently, the glass dissolution in the lead-zinc tailings is reduced, and less mullite is formed, resulting in a decrease in strength, an increase in porosity, and an increase in water absorption.
[0144] Comparative Example 17
[0145] The difference from Example 3 is that the mullite nanopowder is not subjected to activity modification and excitation, but is directly added, and sodium silicate and potassium silicate are added at the same time.
[0146] Comparative Example 18
[0147] The difference from Example 3 is that the mullite nanopowder is not subjected to activity modification and excitation, but is directly added, and sodium silicate and potassium silicate are replaced by sodium oxide and potassium oxide in equal amounts.
[0148] The performance of the ceramsite of Comparative Examples 17 to 18 was tested, and the results are shown in Table 11.
[0149] Table 11 Performance indexes of comparative examples 17 to 18 ceramsite
[0150]
[0151] From the comparison of Comparative Examples 17 to 18 in Table 11 and Example 3, it can be seen that in Comparative Example 17, the mullite nanopowder is not activated, but added to the ceramsite together with sodium silicate and potassium silicate, which leads to a decrease in its strength and an increase in water absorption. This shows that the early mutual activation of the mullite is crucial to the improvement of the overall performance of the ceramsite. Comparative Example 18 uses potassium oxide and sodium oxide to promote dissolution, which is not much different from low modulus sodium silicate and potassium silicate, but there is no bonding structure formed by sodium silicate and potassium silicate, so the ceramsite has lower strength and higher water absorption.
Claims
1. A lead-zinc tailings ceramsite, characterized in that: It is mainly made of the following raw materials by weight: 100 parts of lead-zinc tailings; 20-30 parts of limestone tailings; 6-8 parts of active mullite nano powder; 1-3 parts of glass powder; 8 to 12 parts of dry sludge powder.
2. The lead-zinc tailings ceramsite according to claim 1, characterized in that The active mullite nano powder is prepared by uniformly dispersing mullite particles in a mixed solution of sodium silicate and potassium silicate, heating the solution and then grinding the solution.
3. The lead-zinc tailings ceramsite according to claim 2, characterized in that The mass ratio of the mullite particles to sodium silicate and potassium silicate is 1:(1-2):(3-5); The particle size of the mullite particles is 50-100 nm, the concentration of the mixed solution of sodium silicate and potassium silicate is 5wt%-15wt%, and the modulus of sodium silicate and potassium silicate is not higher than 2; The heating temperature is 300-600°C; The particle size of the active mullite nano powder is 200-400 nm.
4. The lead-zinc tailings ceramsite according to claim 1, characterized in that The specific surface area of the lead-zinc tailings is 800-1000m 2 / kg.
5. The lead-zinc tailings ceramsite according to claim 1, characterized in that The specific surface area of the limestone tailings is not less than 200m 2 / kg.
6. The lead-zinc tailings ceramsite according to claim 1, characterized in that: The specific surface area of the glass powder is not less than 300m 2 / kg.
7. The lead-zinc tailings ceramsite according to claim 1, characterized in that The specific surface area of the dry sludge powder is not less than 200m 2 / kg.
8. A method for preparing lead-zinc tailings ceramsite according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) mixing lead-zinc tailings, limestone tailings, activated mullite nanopowder, glass micropowder and dry sludge powder raw materials uniformly according to parts by mass, and adding water to prepare a ceramsite embryo body; (2) heating the ceramsite embryo to 900-980° C. and maintaining it for 5-8 min; then heating it to 1200-1300° C. and maintaining it for 8-10 min; (3) Cooling to 1150-1100°C and maintaining for 5-10 min; then cooling to 1080-1000°C and maintaining for 5-10 min; then cooling to 950-900°C and maintaining for 5-10 min; finally, slowly cooling to room temperature to obtain lead-zinc tailings ceramsite.
9. The preparation method according to claim 8, characterized in that: The preparation method of the active mullite nano powder is as follows: after the mullite particles are evenly dispersed in a sodium silicate solution and a potassium silicate mixed solution, the particles are dried at a high temperature until the quality is stable, and then ground to 200-400nm under completely dry conditions to obtain the active mullite nano powder.
10. The preparation method according to claim 8, characterized in that: In step (3), the temperature is finally slowly cooled to room temperature, and the cooling rate is not higher than 10°C / min.
Citation Information
Patent Citations
Biological ceramisite filter material made of vulcanized lead zinc ore flotation tailings, and preparation method thereof
CN103086741A
Heavy metal poly-hole adsorption material and preparation method thereof
CN105126760A
Method and system for preparing light ceramsite by using heavy metal tailings
CN115636687A
Hollow thermal insulation ceramsite and preparation method thereof
CN115710136A
Method of treating substrate and substrate treating apparatus performing the same
KR1020230006694A
Cited By
Method for preparing ceramsite from molybdenum tailings
CN120574004A
Method for preparing ceramsite by using molybdenum tailings
CN120574004B
Preparation method of high-strength heavy metal cured geopolymer based on lead-zinc tailings
CN121573918A